Predicting Soil Erosion Using the Soil and Water Assessment Tool (SWAT) Model in Giritengah Catchment Area - Muhammad Zaki Rifqian Hakim; Ambar Kusumandari (Sriwijaya Journal of Environment, 2023)
Giritengah catchment is 5 km to the southwest of Borobudur Temple and is an area that has been designated as a buffer zone which acts as a support zone for tourism activities in the Borobudur Area. The purpose of this study is to predict erosion in the Giritengah catchment and develop a scenario for the application of the right Soil and Water Conservation (SWC) techniques to reduce erosion in the Giritengah catchment. Erosion estimation is carried out using the Soil and Water Assessment Tool (SWAT) model. The results showed  that the average amount of erosion is 30.7 tons/ha/year with the highest average erosion being on dry land use. The classification of the predominant Erosion Hazard Level is in the very low, low and heavy classes. The application of the right SWC technique in the form of bench and ridge terraces structure is expected to be able to reduce erosion that occurs in the Giritengah catchment to very low Erosion Hazard Level (EHL) classes reaching 60.4% of the total area and eliminate heavy EHL classes.